High-temperature adjustable sintering polycrystalline silver powder and preparation method thereof

By using a combination of ferrous sulfate and superdispersed dosage-type protective agent, high-temperature adjustable sinterable polycrystalline silver powder was prepared, which solved the problems of poor sintering activity and toxic substances in the prior art, and achieved multi-scene adaptation and efficient conductive properties of silver powder.

CN119703109APending Publication Date: 2025-03-28NANTONG LIANSHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411946234.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, spherical silver powder has poor sintering activity and cannot adapt to conductive pastes in different application scenarios, and toxic organic matter is easily generated during the production process.

Method used

Ferrous sulfate is used as a reducing agent and combined with a superdispersed dosage-based protective agent. Through the formation of neutralization liquid and pH adjustment, the density and self-assembly of silver powder are controlled to prepare high-temperature adjustable sinterable polycrystalline silver powder.

Benefits of technology

It realizes the adaptability of silver powder in different application scenarios, improves sintering activity and conductivity, reduces the production of toxic substances, and has broad application and industrialization prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703109A_ABST
    Figure CN119703109A_ABST
Patent Text Reader

Abstract

The invention provides high-temperature adjustable sintering polycrystalline silver powder and a preparation method thereof, and belongs to the technical field of conductive silver powder. The preparation method comprises the following steps: obtaining a silver nitrate solution; obtaining a ferrous sulfate reduction solution; mixing ferrous sulfate with a protective agent to obtain a neutralization solution; the neutralization solution serves as a base solution, the silver nitrate solution and the ferrous sulfate reduction solution are added under the stirring condition, and a silver powder reduction product is obtained; and the silver powder reduction product is subjected to sedimentation, cleaning, drying and grinding to obtain the silver powder. According to the method, ferrous sulfate serves as a reducing agent, the reaction process is mild, different crystal forms can be effectively and controllably synthesized by combining with different ultra-dispersion type protective agents, and the density of prepared silver powder particles is adjustable. The adaptability of the silver powder in different application scenes is achieved, and the silver powder has wide application and industrialization prospects in various conductive pastes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silver powder, and in particular relates to a high-temperature adjustable sintering polycrystalline silver powder and a preparation method thereof. Background Art

[0002] Spherical silver powder is a nanomaterial with unique physical and chemical properties. Its spherical shape provides excellent dispersibility and a high specific surface area, which makes spherical silver powder have significant advantages in electrical conductivity, thermal conductivity, and antibacterial properties. It is widely used in electronics, optics, catalysis, medicine and other fields. Among them, there are various methods for preparing spherical silver powder, including chemical reduction, liquid phase reduction, spray thermal decomposition, evaporation condensation, etc. In the process of preparing spherical silver powder, controlling the particle size, particle size distribution, morphology and purity of the silver powder is a key factor. These characteristics directly affect the application performance of the silver powder. For example, in the electronics industry, the particle size and distribution of the silver powder will affect the conductive properties and the stability of the silver paste.

[0003] Currently, silver powder is mostly prepared by liquid phase reduction method, in which the reducing agent adopts traditional ascorbic acid, hydrazine hydrate, formaldehyde, etc., which are easy to produce a large amount of toxic organic matter in the later production process. Dispersants mostly use citric acid, polyethylene glycol, sodium hexadecylbenzene sulfonate, sodium hexadecyl sulfate, etc. This type of fatty acid dispersant has limited dispersibility for silver powder, and the silver powder formed by the combination of the above-mentioned reducing agent and dispersant has poor sintering activity and cannot be adapted to the conductive slurry of different application scenarios. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a high-temperature adjustable sintering polycrystalline silver powder and a preparation method thereof.

[0005] In one aspect of the present disclosure, a method for preparing high-temperature adjustable sintering polycrystalline silver powder is provided, the preparation method comprising:

[0006] Obtain silver nitrate solution;

[0007] obtaining a ferrous sulfate reducing solution;

[0008] Mixing ferrous sulfate with a protective agent to obtain a neutralizing solution;

[0009] Using the neutralization solution as the base solution, adding the silver nitrate solution and the ferrous sulfate reduction solution under stirring conditions to obtain a silver powder reduction product;

[0010] The silver powder reduction product is subjected to sedimentation, washing, drying and polishing to obtain silver powder.

[0011] Optionally, the concentration of the silver nitrate solution is 210-420 g / L.

[0012] Optionally, the concentration of the ferrous sulfate reducing solution is 750-2200 g / L.

[0013] Optionally, the molar ratio of the ferrous sulfate reducing solution to the silver nitrate solution is (4-6):1.

[0014] Optionally, in the neutralization solution, the concentration of ferrous sulfate is 75-220 g / L, and the concentration of the protective agent is 150-300 g / L.

[0015] Optionally, the protective agent is a hyperdispersant.

[0016] Optionally, the hyperdispersant is one or a combination of modified N-vinyl pyrrolidone, styrene maleic anhydride block graft copolymer, polyester hyperdispersant, polyvinyl pyrrolidone, polyvinyl alcohol 17-99.

[0017] Optionally, the method further comprises:

[0018] A pH adjuster is added to the neutralization solution to adjust the pH value of the solution to 2-5.

[0019] Optionally, the pH adjuster is sulfuric acid.

[0020] Another aspect of the present disclosure provides a high-temperature adjustable sinterable polycrystalline silver powder, which is prepared by the preparation method of the high-temperature adjustable sinterable polycrystalline silver powder described above.

[0021] The present disclosure proposes a high-temperature adjustable sintering polycrystalline silver powder and a preparation method thereof. The preparation method comprises: obtaining a silver nitrate solution; obtaining a ferrous sulfate reducing solution; mixing ferrous sulfate with a protective agent to obtain a neutralizing solution; using the neutralizing solution as a base liquid, adding the silver nitrate solution and the ferrous sulfate reducing solution under stirring conditions to obtain a silver powder reduction product; the silver powder reduction product is subjected to sedimentation, washing, drying, and polishing to obtain silver powder. The present disclosure uses ferrous sulfate as a reducing agent, and its reaction process is relatively mild. Different crystal forms can be effectively and controllably synthesized by combining with different superdispersant protective agents, and the obtained silver powder particles have adjustable density. The adaptability of silver powder in different application scenarios is achieved, and it has broad application and industrialization prospects in various conductive pastes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flowchart of a method for preparing high-temperature adjustable sintering polycrystalline silver powder according to a specific embodiment of the present disclosure;

[0023] Figure 2 This is an electron microscope image of the silver powder prepared in Example 1 of the present disclosure;

[0024] Figure 3This is an electron microscope image of the sintered silver powder prepared in Example 1 of the present disclosure;

[0025] Figure 4 This is an electron microscope image of the silver powder prepared in Example 2 of the present disclosure;

[0026] Figure 5 This is an electron microscope image of the sintered silver powder prepared in Example 2 of the present disclosure;

[0027] Figure 6 This is an electron microscope image of the silver powder prepared in Example 3 of the present disclosure;

[0028] Figure 7 This is an electron microscope image of the sintered silver powder prepared in Example 3 of the present disclosure;

[0029] Figure 8 This is an electron microscope image of the sintered silver powder prepared in Comparative Example 1 of the present disclosure;

[0030] Fig. 9 This is an electron microscope image of the sintered silver powder prepared in Comparative Example 2 of the present disclosure. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0032] like Figure 1 As shown, the present disclosure provides a method S100 for preparing high-temperature adjustable sintering polycrystalline silver powder, which specifically includes the following steps S110 to S130:

[0033] S110. Obtain a silver nitrate solution.

[0034] Specifically, silver nitrate is prepared with deionized water to form a silver nitrate solution with a concentration of 210-420 g / L, and the concentration may be further preferably 250-350 g / L, for example, 250 g / L, 300 g / L, 350 g / L, etc.

[0035] S120, obtaining a ferrous sulfate reduction solution.

[0036] Specifically, ferrous sulfate is prepared with deionized water to form a ferrous sulfate reducing solution with a concentration of 750-2200 g / L, and its concentration may be further preferably 1000-1500 g / L, for example, 1000 g / L, 1150 g / L, 1200 g / L, 1350 g / L, 1450 g / L, 1500 g / L, etc.

[0037] S130, mixing ferrous sulfate with a protective agent to obtain a neutralization solution.

[0038] Specifically, ferrous sulfate with a concentration of 75-220 g / L and a protective agent with a concentration of 150-300 g / L are prepared with deionized water, and the 75-220 g / L ferrous sulfate and the 150-300 g / L protective agent are mixed to obtain a neutralized solution, wherein the volume ratio of ferrous sulfate to the protective agent is preferably 1:2.

[0039] In some preferred embodiments, the concentration of ferrous sulfate may be further preferably 100-175 g / L, and the concentration of the protective agent may be further preferably 180-250 g / L.

[0040] In other preferred embodiments, the protective agent is a hyperdispersant, which may preferably be one or a combination of modified N-vinyl pyrrolidone (for example, modified N-vinyl pyrrolidone containing a vinyl acetate group), styrene maleic anhydride block graft copolymer, polyester hyperdispersant (non-linear), polyvinyl pyrrolidone, and polyvinyl alcohol 17-99, without specific limitation.

[0041] In other preferred embodiments, the average molecular weight of the protective agent should be selected between 2-5W.

[0042] In some other preferred embodiments, sulfuric acid is further added to the neutralization solution in step S130 as a pH regulator to control the pH value of the neutralization solution between 2-5.

[0043] It should be noted that the deionized water used in the silver nitrate solution, ferrous sulfate reduction solution, and neutralization solution in steps S110, S120, and S130 all refer to pure water with a salt content of less than 0.3 mg / L and an electrical conductivity of less than 0.2 μs / cm.

[0044] In step S130, the neutralization solution formed by ferrous sulfite and the protective agent is beneficial to improving the quality of crystal growth, the density of the silver interface after sintering, and the sintering activity.

[0045] S140, using the neutralization solution as a base solution, adding the silver nitrate solution and the ferrous sulfate reducing solution under stirring conditions to obtain a silver powder reduction product.

[0046] In some preferred embodiments, the molar ratio of the ferrous sulfate reducing solution to the silver nitrate solution is (4-6):1, for example, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, etc. may be preferred.

[0047] In some other preferred embodiments, the stirring speed of step S140 is preferably 150-300 rpm. The time for adding the silver nitrate solution and the ferrous sulfate reducing solution into the neutralizing solution is controlled to be 7-15 minutes.

[0048] It should be noted that in step S140, the temperature of the silver nitrate solution, the ferrous sulfate reducing solution, and the neutralizing solution before the reaction can be controlled at 20-30°C.

[0049] S150, the silver powder reduction product is precipitated, washed, dried and polished to obtain silver powder.

[0050] In some preferred embodiments, the cleaning in step S150 can be performed with ultrapure water for 2 to 3 times, and then with anhydrous alcohol for 1 to 2 times, and the drying can be performed in a forced air drying oven at 40 to 60° C. for 16 to 24 hours.

[0051] In this embodiment, ferrous sulfate is used as a reducing agent, and the reaction process is relatively mild. The ferrous sulfate can be effectively and controllably synthesized into different crystal forms by combining with different superdispersant protective agents, and the density of the obtained silver powder particles is adjustable. At the same time, the pH value of the reaction solution is adjusted by sulfuric acid to obtain silver particles with different self-assembly modes, which meets the adaptability of silver powder in different application scenarios and has broad application and industrialization prospects in various conductive pastes.

[0052] Another aspect of the present disclosure provides a high-temperature adjustable sinterable polycrystalline silver powder, which is prepared by the preparation method given above. Please refer to the above description for the specific process, which will not be repeated here.

[0053] The particle size D50 of the silver powder obtained in the present disclosure is 0.7 to 3 μm, and the specific surface area is 0.3 to 1.4 m 2 / g.

[0054] The preparation method of high temperature adjustable sintering polycrystalline silver powder will be further described below in conjunction with specific examples:

[0055] Example 1

[0056] (1) Preparation of silver nitrate solution: Prepare 105 L of 300 g / L silver nitrate solution A with deionized water and keep the temperature at 25° C. before the reaction;

[0057] (2) Preparation of reducing solution: 105 L of 1350 g / L ferrous sulfate reducing solution B was prepared with deionized water and kept at 25°C before the reaction. That is, the molar ratio of ferrous sulfate to silver nitrate was about 5:1;

[0058] (3) Preparation of neutralization solution: Prepare with deionized water, mix 15 L of 100 g / L ferrous sulfate with 30 L of 214 g / L protective agent to obtain neutralization solution C, add sulfuric acid to adjust the pH to 4.5, and keep the temperature at 25°C before the reaction;

[0059] In step 3, the protective agent is modified N-vinyl pyrrolidone containing vinyl acetate groups, with an average molecular weight of 3.7W.

[0060] It should be noted that the deionized water used in the above steps (1-3) has a salt content of 0.28 mg / L and a conductivity of 0.1 μs / cm.

[0061] (4) Preparation of silver powder reduction product: Use neutralization solution C as the base liquid and control the stirring speed to 200 rpm. Add silver nitrate solution A and ferrous sulfate reduction solution B at the same time. The addition time of these two solutions is controlled within 12 minutes;

[0062] (5) Post-treatment of silver powder: The precipitate obtained after sedimentation in step (4) is washed three times with ultrapure water, then washed twice with anhydrous alcohol, dried in a forced air drying oven at 55° C. for 20 hours, and then ground into powder to obtain a silver powder product.

[0063] like Figure 2 and Figure 3 As shown, the silver interface after sintering is relatively dense, the contact between the silver particles is closer, the stacking is compact, the overall sintering activity is excellent, and a continuous conductive network can be formed, which is beneficial to the improvement of the conductive properties of the silver paste.

[0064] As shown in Table 1, the silver powder of this embodiment has D10=0.961 μm, D50=1.31 μm, D90=2.202 μm, D100=3.623 μm, and a specific surface area of ​​0.768 m 2 / g, tap density is 6.01g / cc, and ablation is 0.65%.

[0065] The silver powder of this embodiment is mixed with glass powder, organic carrier and solvent, and silver paste is prepared by three rollers. It is printed on the silicon substrate by screen printing, sintered to form gate lines, and the performance of the silicon wafer is tested. As shown in Table 2, the contact resistivity of the silicon wafer of this embodiment is 1.3mΩ·cm 2 , the line resistivity is 1.6Ω·cm.

[0066] Example 2

[0067] (1) Preparation of silver nitrate solution: Prepare 100 L of 300 g / L silver nitrate solution A with deionized water and keep the temperature at 25° C. before the reaction;

[0068] (2) Preparation of reducing solution: 100 L of 1350 g / L ferrous sulfate reducing solution B was prepared with deionized water and kept at 25°C before the reaction. That is, the molar ratio of ferrous sulfate to silver nitrate was about 5:1;

[0069] (3) Preparation of neutralization solution: Prepare with deionized water, mix 15 L of 100 g / L ferrous sulfate with 30 L of 214 g / L protective agent to obtain neutralization solution C, add sulfuric acid to adjust the pH to 4.5, and keep the temperature at 25°C before the reaction;

[0070] In step 3, the protective agent is a styrene maleic anhydride block graft copolymer with an average molecular weight of 4.3W.

[0071] It should be noted that the deionized water used in the above steps (1-3) has a salt content of 0.28 mg / L and a conductivity of 0.1 μs / cm.

[0072] (4) Preparation of silver powder reduction product: Use neutralization solution C as the base liquid and control the stirring speed to 200 rpm. Add silver nitrate solution A and ferrous sulfate reduction solution B at the same time. The addition time of these two solutions is controlled within 12 minutes;

[0073] (5) Post-treatment of silver powder: The precipitate obtained after sedimentation in step (4) is washed three times with ultrapure water, then washed twice with anhydrous alcohol, dried in a forced air drying oven at 55° C. for 20 hours, and then ground into powder to obtain a silver powder product.

[0074] like Figure 4 and Figure 5 As shown, the silver interface after sintering at the same temperature as Example 1 is denser, the contact between the silver particles is closer, the stacking is compact, the overall sintering activity is excellent, and a continuous conductive network can be formed, which is beneficial to the improvement of the conductive performance of the silver paste.

[0075] As shown in Table 1, the silver powder of this embodiment has D10=1.112 μm, D50=1.563 μm, D90=2.643 μm, D100=4.514 μm, and a specific surface area of ​​0.604 m 2 / g, tap density is 5.99g / cc, and ablation is 0.42%.

[0076] The silver powder of this embodiment is mixed with glass powder, organic carrier and solvent, and silver paste is prepared by three rollers, which is printed on the silicon substrate by screen printing, sintered under the same conditions as in Example 1 to form gate lines, and the performance of the silicon wafer is tested. As shown in Table 2, the contact resistivity of the silicon wafer in this embodiment is 1.5 mΩ·cm 2 , the line resistivity is 1.9Ω·cm.

[0077] Example 3

[0078] (1) Preparation of silver nitrate solution: Prepare 100 L of 300 g / L silver nitrate solution A with deionized water and keep the temperature at 25° C. before the reaction;

[0079] (2) Preparation of reducing solution: 100 L of 1350 g / L ferrous sulfate reducing solution B was prepared with deionized water and kept at 25°C before the reaction. That is, the molar ratio of ferrous sulfate to silver nitrate was about 5:1;

[0080] (3) Preparation of neutralization solution: Prepare with deionized water, mix 15 L of 100 g / L ferrous sulfate with 30 L of 214 g / L protective agent to obtain neutralization solution C, add sulfuric acid to adjust the pH to 4.5, and keep the temperature at 25°C before the reaction;

[0081] In step 3, the protective agent is polyvinyl alcohol 17-99: polyester type hyperdispersant in a molar ratio of 1:1, and the average molecular weight is 4.5W.

[0082] It should be noted that the deionized water used in the above steps (1-3) has a salt content of 0.28 mg / L and a conductivity of 0.1 μs / cm.

[0083] (4) Preparation of silver powder reduction product: Use neutralization solution C as the base liquid and control the stirring speed to 200 rpm. Add silver nitrate solution A and ferrous sulfate reduction solution B at the same time. The addition time of these two solutions is controlled within 12 minutes;

[0084] (5) Post-treatment of silver powder: The precipitate obtained after sedimentation in step (4) is washed three times with ultrapure water, then washed twice with anhydrous alcohol, dried in a forced air drying oven at 55° C. for 20 hours, and then ground into powder to obtain a silver powder product.

[0085] like Figure 6 and Figure 7 As shown, the silver interface after sintering at the same temperature as Example 1 is denser, the contact between the silver particles is closer, the stacking is compact, the overall sintering activity is excellent, and a continuous conductive network can be formed, which is beneficial to the improvement of the conductive performance of the silver paste.

[0086] As shown in Table 1, the silver powder of this embodiment has D10=1.214 μm, D50=1.695 μm, D90=2.959 μm, D100=5.113 μm, and a specific surface area of ​​0.544 m 2 / g, tap density is 6.4g / cc, and ablation is 0.32%.

[0087] The silver powder of this embodiment is mixed with glass powder, organic carrier and solvent, and silver paste is prepared by three rollers, which is printed on the silicon substrate by screen printing, sintered under the same conditions as in Example 1 to form gate lines, and the performance of the silicon wafer is tested. As shown in Table 2, the contact resistivity of the silicon wafer in this embodiment is 1.8 mΩ·cm 2 , the line resistivity is 1.7Ω·cm.

[0088] Comparative Example 1

[0089] This comparative example uses commercially available spherical silver powder, as shown in Table 1. The silver powder has D10 = 1.296 μm, D50 = 2.015 μm, D90 = 2.846 μm, D100 = 5.074 μm, and a specific surface area of ​​0.568 m 2 / g, tap density is 5.63g / cc, and ablation is 0.58%.

[0090] The silver powder of this comparative example was mixed with glass powder, organic carrier and solvent, and silver paste was prepared by three rollers. The silver paste was printed on a silicon substrate by screen printing, and sintered to form gate lines under the same conditions as in Example 1, and the performance of the silicon wafer was tested. As shown in Table 2, the contact resistivity of the silicon wafer of this comparative example is 2.4 mΩ·cm 2 , the line resistivity is 2.1Ω·cm.

[0091] like Figure 8 As shown, the silver powder sintered at the same temperature as Example 1 forms a connection after sintering, but the uniformity is poor, the stacking is not tight, there are many gaps, and a dense conductive network cannot be formed, which affects the electrical properties of the slurry, and a good contact with the silicon wafer cannot be formed, which is ultimately reflected in the contact resistivity and line resistivity being higher than Examples 1-3.

[0092] Comparative Example 2

[0093] (1) Preparation of silver nitrate solution: Prepare 100 L of 300 g / L silver nitrate solution A with deionized water and keep the temperature at 25° C. before the reaction;

[0094] (2) Preparation of reducing solution: 100 L of 1350 g / L citric acid reducing solution B was prepared with deionized water and kept at 25°C before the reaction. That is, the molar ratio of ferrous sulfate to silver nitrate was about 5:1;

[0095] It should be noted that the deionized water used in the above step (1-2) has a salt content of 0.28 mg / L and a conductivity of 0.1 μs / cm.

[0096] (3) Preparation of silver powder reduction product: Control the stirring speed to 200 rpm, add silver nitrate solution A and ferrous sulfate reduction solution B, and the addition time of these two solutions is controlled within 12 minutes;

[0097] (4) Post-treatment of silver powder: The precipitate obtained after sedimentation in step (3) is washed three times with ultrapure water, then washed twice with anhydrous alcohol, dried in a forced air drying oven at 55° C. for 20 hours, and then ground into powder to obtain a silver powder product.

[0098] As shown in Table 1, the silver powder of this comparative example has D10=2.896 μm, D50=3.568 μm, D90=4.367 μm, D100=6.219 μm, and a specific surface area of ​​0.506 m 2 / g, tap density is 5.06g / cc, and ablation is 0.30%.

[0099] The silver powder of this comparative example was mixed with glass powder, organic carrier, and solvent, and a silver paste was prepared by three rollers. The silver paste was printed on a silicon substrate by screen printing, and sintered to form a gate line under the same conditions as in Example 1, and the performance of the silicon wafer was tested. As shown in Table 2, the contact resistivity of the silicon wafer of this comparative example is 3.2 mΩ·cm 2 , the line resistivity is 3.6Ω·cm.

[0100] like Fig. 9 As shown, the silver powder sintered at the same temperature as Example 1 almost did not form a sintering connection, the sintering activity was low, and its contact resistivity and line resistivity were significantly higher than those of Examples 1-3.

[0101] Comparative Example 3

[0102] The protective agent in Example 1 was replaced by sodium hexadecyl sulfate, and the other components, parts, process steps, etc. were the same as those in Example 1.

[0103] As shown in Table 1, the silver powder of this comparative example has D10=2.228 μm, D50=2.469 μm, D90=3.810 μm, D100=5.168 μm, and a specific surface area of ​​0.539 m 2 / g, the tap density is 5.87g / cc, the ablation is 0.32%, the silver powder particle size is larger than that in Example 1, and the specific surface area and tap density are reduced.

[0104] As shown in Table 2, the contact resistivity of the silicon wafer in this comparative example is 3.1 mΩ·cm 2 , the line resistivity is 3.0Ω·cm. Compared with Example 1, the line resistivity has increased, and the contact resistivity has increased more significantly, about 2.4 times that of Example 1.

[0105] Comparative Example 4

[0106] The ferrous sulfate in Example 1 was replaced by ascorbic acid, and the other components, parts, process steps, etc. were the same as those in Example 1.

[0107] As shown in Table 1, the silver powder of this comparative example has D10=1.186 μm, D50=2.874 μm, D90=3.452 μm, D100=5.016 μm, and a specific surface area of ​​0.549 m 2 / g, tap density is 5.63g / cc, ablation is 0.59%, the silver powder particle size is larger than that of Example 1, and the specific surface area and tap density are reduced

[0108] As shown in Table 2, the contact resistivity of the silicon wafer in this comparative example is 2.8 mΩ·cm 2 The line resistivity is 3.0Ω·cm. Compared with Example 1, the line resistivity and the contact resistivity have increased to varying degrees.

[0109] Comparative Example 5

[0110] The sulfuric acid in step (3) of Example 1 was replaced by acetic acid, and the pH was adjusted to 4.5. The other components, parts, process steps, etc. were the same as those in Example 1.

[0111] As shown in Table 1, the silver powder of this comparative example has D10=1.983 μm, D50=2.068 μm, D90=3.563 μm, D100=4.687 μm, and a specific surface area of ​​0.513 m 2 / g, the tap density is 5.36g / cc, the ablation is 0.63%, the silver powder particle size is larger than that in Example 1, and the specific surface area and tap density are reduced.

[0112] As shown in Table 2, the contact resistivity of the silicon wafer in this comparative example is 2.6 mΩ·cm 2 The line resistivity is 2.3Ω·cm. Compared with Example 1, both the line resistivity and the contact resistivity increase to varying degrees.

[0113] Table 1 Silver powder properties of various embodiments and comparative examples

[0114]

[0115] Table 2 Silicon wafer properties of various embodiments and comparative examples

[0116]

[0117]

[0118] In summary, according to Examples 1-3 and Comparative Examples 1-5, the silver powder of Examples 1-3 has a smaller particle size, better sintering activity, and can form a continuous conductive network after sintering, and its conductive performance is good. By changing the type of super dispersant, different crystal growth methods and different self-assembly forms of crystals can be achieved, so as to prepare silver powders of different morphologies according to demand. In other words, by the combination of ferrous sulfate reducing agent+super dispersant type protective agent+sulfuric acid pH adjusting agent, high-temperature excellent sintering activity of silver particles is achieved, forming a continuous high-quality conductive network and excellent contact with silicon wafers, and, by using ferrous sulfate as a reducing agent and sulfuric acid as a pH adjusting agent, by selecting different types of protective agents, the self-assembly mode of silver powder can be controlled, and a finer adjustment of sintering activity is achieved on the basis of ensuring excellent sintering activity, and the formula and process are more simplified than the prior art.

[0119] The present disclosure provides a high-temperature adjustable sintering polycrystalline silver powder and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0120] First, compared with conventional reducing agents such as ascorbic acid, hydrazine hydrate, and formaldehyde, the present invention uses ferrous sulfate as a reducing agent, and the reaction process is relatively mild. Different crystal forms can be effectively and controllably synthesized by combining with different superdispersant protective agents, and the density of the obtained silver powder particles can be adjusted. It also helps to reduce a large amount of toxic and harmful substances generated in the later production;

[0121] Second, compared with conventional fatty acid dispersants such as citric acid and sodium hexadecyl sulfate, the present invention uses a super dispersant, which helps to improve the dispersibility of the silver powder, and by combining the super dispersant with ferrous sulfite to form a neutralizing solution, the formed silver powder has excellent high-temperature sintering activity, which helps to form a high-quality conductive network and excellent contact with the silicon wafer;

[0122] Third, by selecting different types of protective agents and combining them with ferric sulfite, the self-assembly mode of silver powder can be controlled, and silver particles with different self-assembly modes can be obtained. On the basis of ensuring excellent sintering activity, more precise adjustment of sintering activity can be achieved to meet the silver paste requirements of different application scenarios;

[0123] Fourth, by using sulfuric acid as a pH regulator, the prepared silver powder is easier to control during the microscopic crystal growth process.

[0124] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing high-temperature adjustable sintering polycrystalline silver powder, characterized in that: The preparation method comprises: Obtain silver nitrate solution; obtaining a ferrous sulfate reducing solution; Mixing ferrous sulfate with a protective agent to obtain a neutralizing solution; Using the neutralization solution as the base solution, adding the silver nitrate solution and the ferrous sulfate reduction solution under stirring conditions to obtain a silver powder reduction product; The silver powder reduction product is subjected to sedimentation, washing, drying and polishing to obtain silver powder.

2. The preparation method according to claim 1, characterized in that: The concentration of the silver nitrate solution is 210-420 g / L.

3. The preparation method according to claim 1, characterized in that: The concentration of the ferrous sulfate reducing solution is 750-2200 g / L.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the ferrous sulfate reducing solution to the silver nitrate solution is (4-6):

1.

5. The preparation method according to claim 1, characterized in that: In the neutralization solution, the concentration of ferrous sulfate is 75-220 g / L, and the concentration of the protective agent is 150-300 g / L.

6. The preparation method according to claim 5, characterized in that: The protective agent is a hyperdispersant.

7. The preparation method according to claim 6, characterized in that: The super dispersant is one or a combination of modified N-vinyl pyrrolidone, styrene maleic anhydride block graft copolymer, polyester super dispersant, polyvinyl pyrrolidone, polyvinyl alcohol 17-99.

8. The preparation method according to claim 1, characterized in that: The method further comprises: A pH adjuster is added to the neutralization solution to adjust the pH value of the solution to 2-5.

9. The preparation method according to claim 8, characterized in that: The pH adjuster is sulfuric acid.

10. A high temperature adjustable sinterable polycrystalline silver powder, characterized in that: The polycrystalline silver powder is prepared by the method for preparing the high temperature adjustable sintering property as described in any one of claims 1 to 9.